2008
DOI: 10.4049/jimmunol.181.9.6316
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of CD30L/CD30 Signaling by T-T Cell Interaction in Th1 Response against Mycobacterial Infection

Abstract: A CD30 ligand (CD30L, CD153) is a type II membrane-associated glycoprotein belonging to the TNF family. To illustrate the potential role of CD30L in CD4+ Th1 cell responses, we investigated the fate of Ag-specific CD4+ T cells in CD30L-deficient (CD30L−/−) mice after Mycobacterium bovis bacillus Calmette-Guérin (BCG) infection. The number of bacteria was significantly higher in organs of CD30L−/− mice than in wild-type (WT) mice 4 wk postinfection. The numbers of purified protein derivative- or Ag85B-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 50 publications
(43 reference statements)
6
51
0
Order By: Relevance
“…Consistent with a previous report (36), a few but significant number of CD4 + T cells of spleen, MLN, and LPLs expressed CD30L in naive mice. CD30L expression on CD4 + T cells, especially in LPLs, was significantly increased on day 5 in DSS-induced acute colitis and on day 25 in DSS-induced chronic colitis (Fig.…”
Section: Increased Cd30 Ligand Expression On Cd4 + T Cells In Dss-indsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with a previous report (36), a few but significant number of CD4 + T cells of spleen, MLN, and LPLs expressed CD30L in naive mice. CD30L expression on CD4 + T cells, especially in LPLs, was significantly increased on day 5 in DSS-induced acute colitis and on day 25 in DSS-induced chronic colitis (Fig.…”
Section: Increased Cd30 Ligand Expression On Cd4 + T Cells In Dss-indsupporting
confidence: 93%
“…The level of Th1-type cytokine IFN-g in T-LPLs was significantly lower in OXA-or TNBS-treated CD30L 2/2 mice than that in WT mice (29). We also found that CD30L 2/2 mice were susceptible to infection with bacillus Calmette-Guérin in association with reduced Th1 responses (36). These results suggested that CD30L/CD30 signaling is linked to Th1 cell responses and Th1-associated diseases.…”
Section: Discussionsupporting
confidence: 50%
“…These results were interesting because, at cell line levels, elevated CD30 expression is considered to be one of the causes of constitutive NF-kappa B activation in ATL cells, thereby resulting in ATL development (Higuchi et al, 2005). Tang et al reported that CD30-CD30L signaling are important for T-cell regulation (Tang et al, 2008). Based on these results, in the microenvironment, it is conceivable that ATL stem cells produce sIL-2R and sCD30 to prevent activating T cell death by excess IL-2R signaling and cell death caused by CD30-CD30L interaction (Pornkuna et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent studies indicated that CD30L/CD30 signaling is also linked to Th1 or regulatory T cell responses and their associated diseases (30)(31)(32)(33)(34)(35). We have recently found that CD30L/CD30 signaling executed by T cell-T cell interaction plays a novel role in Th1 and Th17 cell differentiation in vitro and in vivo (36)(37)(38). In this regard, CD30L/CD30 signaling may be dispensable for differentiation of a specific Th cell subset in a physiological pathway, while it may be required for the activation and/or amplification of T cells irrespective of the T cell subset in the periphery.…”
mentioning
confidence: 97%
“…Recently, we and others reported that CD30L and CD30 play an important role in acquired immunity against mycobacterial infection by amplifying the Th1 response (32,36). However, the potential role of CD30L/CD30 signaling in controlling host defense through activation of IL-17A-producing T cells against mycobacterial infection is unknown.…”
mentioning
confidence: 98%